Employee Well Being and Knowledge Sharing Behavior among Employees of Saudi Aramco - Alghamdi, Mansour; Siew-Imm Ng; Jo Ann Ho; Ramachandran, Sridar; Abdulsamad Ali, AKRAM (Advances in Social Sciences Research Journal, 2021)
The oil and gas industries in Saudi Arabia requires research attention regarding Knowledge Sharing Behavior (KSB), as the industries suffer from compromised KSB which may adversely affect sustainability in knowledge advancement and competitive advantage. There are research gaps in the antecedents of KSB such as 1) dimensions of Employee Well Being (EWB) being contextual and untested in Saudi Arabia; 2) leadership style and culture that motivate KSB were unknown. Thus, this study aims to uncover EWB, leadership and culture factors that determine KSB. A total of 260 Aramco employees’ responses were analyzed using SPSS. The study has found physical well-being, psychological well-being, social well-being, benevolent leadership, and innovative organizational culture contributed to increasing KSB among Saudi Aramco employees. Theoretical and managerial implications were then discussed.